Pengaruh Variasi Timing Opening Angle Terhadap Jumlah Weft Stop pada Pertenunan Kain dengan Anyaman Keper 2/1 1 di Mesin Air Jet Loom - Filly Pravitasari; Afriani Kusumadewi (Universitas Insan Cendekia Mandiri, 2021)
In the weaving process, the process of launching the weft yarn is an important thing to consider. One of the obstacles that often occurs in the process of launching feed using a water jet loom machine is the amount of feed stuck (weft stop). The cause of the weft stop is because the process of opening the warp mouth is not clean and the weft thread slides inappropriately or too fast so that the warp mouth is in a small condition. Variations in timing opening angle of 700, 800 and 900 determine the size of the warp mouth opening, the time the weft will slide and the time the weft will arrive. From the three variations of the timing opening angle, the number of weft stops at the timing opening angle of 800 is smaller than the timing opening angle of 700 and 900, which is namely the number of big loops 0.6 times and end loops 0.8 times per hour.